PENGUATAN NILAI ISLAM MELALUI PENYUSUNAN BUKU AJAR KEAGAMAAN PADA GENERASI MUDA SAMIN MARGOMULYO BOJONEGORO - Fatihatus Sakinah; Nur Alamin; Nabil Fithran; Islahul Akmali (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This community service research aims to strengthen religious education in Kampung Samin, Margomulyo Village, Bojonegoro Regency, through assistance in developing teaching materials at the Al-Qur'an Education Park (TPQ). It uses a Community-Based Participatory Research (CBPR) approach. The program involves 17 TPQ teachers with heterogeneous educational backgrounds and students aged 7–12 years. The results show a significant transformation: the learning method shifted from traditional bandongan to age-based classical learning, teachers were able to develop contextual modules covering basic fiqh, tajwid, and Arabic writing, and students showed increased motivation and active participation. CBPR also encouraged collaboration among teachers, strengthened pedagogical capacity, and fostered a sense of ownership of the products produced. In addition to producing teaching media, this program shifted the understanding of Islam in the Samin community from a mere formal identity to a more substantive internalization of values among the younger generation